Representasi Nilai Moral Dalam Film My Nerd Girl Serta Implikasinya Terhadap Pembelajaran Drama Di Sma - Risckha Ronanti; Paul Diman; Indra Perdana; Petrus Poerwadi; Misnawati Misnawati (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
The general research objective is to get an overview of the moral values ​​in a film and to find out the implications for drama learning in high school. This study uses a qualitative descriptive analysis approach, in which the researcher records carefully and carefully the data in the form of words, sentences, pictures, and videos. The use of a descriptive qualitative approach in this study aims to describe and understand the moral values ​​in the film My Nerd Girl. The film My Nerd Girl provides many illustrations regarding moral values ​​that can be presented as role models for students at school. Therefore, in learning drama films this can be presented as an alternative teaching material, especially in discussions about examining the characteristics of elements and linguistic rules in drama texts in the form of scripts or stages and presenting plays in the form of stages or scripts. Researchers found 45 data on moral values ​​in the film My Nerd Girl and have described their implications for drama learning in high school. The most common moral values ​​found were the moral values ​​of helping each other, the moral values ​​of being responsible and the moral values ​​of cruelty, while the fewest were the moral values ​​of persecution and the moral values ​​of revenge.